Capacitor

JP7632291B2Active Publication Date: 2025-02-19KYOCERA CORP
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
JP2021548784
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Priority Date
2019-09-26
Filing Date
2020-09-10
Publication Date
2025-02-19
Estimated Expiration
2040-09-10

Smart Images

  • Figure 0007632291000002
    Figure 0007632291000002
  • Figure 0007632291000003
    Figure 0007632291000003
  • Figure 0007632291000004
    Figure 0007632291000004
Patent Text Reader

Abstract

This capacitor is provided with a capacitor body in which dielectric layers and internal electrode layers are alternately layered in multiple layers. The dielectric layers are primarily composed of multiple crystal particles made of barium titanate as a main component, and the dielectric layers contain magnesium, rare earth elements, and manganese. At least one of magnesium, rare earth elements, and manganese is present in the form of single-element oxide particles.
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present disclosure relates to a stacked capacitor. [Background technology]

[0002] An example of the prior art is described in Patent Document 1. [Prior art documents] [Patent documents]

[0003] [Patent Document 1] JP 2011-132056 A Summary of the Invention

[0004] The capacitor of the present disclosure includes a capacitor body in which dielectric layers and internal electrode layers are alternately laminated in multiple layers, and the dielectric layers are mainly composed of multiple crystal particles whose main component is barium titanate, and contain magnesium, rare earth elements, and manganese, with at least one of the magnesium, rare earth elements, and manganese being present as oxide particles containing the element as a single substance. [Brief description of the drawings]

[0005] The objects, features and advantages of the present disclosure will become more apparent from the following detailed description and drawings.

[0006] [Figure 1] 1 is an external perspective view of a capacitor shown as an example of an embodiment; [Diagram 2] 2 is a cross-sectional view taken along line ii-ii in FIG. 1. [Diagram 3] FIG. 3 is an enlarged cross-sectional view of a portion P1 in FIG. 2. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0007] First, in recent years, in stacked capacitors (hereinafter referred to as capacitors), which are capacitors having a configuration based on the capacitor of the present disclosure, the dielectric layers and internal electrode layers have been made thinner in order to reduce size and increase capacitance.

[0008] Thinning the dielectric layer in a capacitor is one way to increase the capacitance of the capacitor. However, as the thickness of the dielectric layer becomes thinner, it becomes more difficult to ensure insulation. If a voltage is applied to a capacitor and this state is continued for a long time, the capacitor will generate heat, the temperature will rise, and the reliability will tend to decrease. In other words, if an electronic device is operated and a voltage is continuously applied to the capacitor, the temperature of the capacitor will gradually rise due to the continuous application of voltage. Taking a reliability test as an example, the capacitor will be constantly undergoing a high-temperature load life test.

[0009] The capacitor of the embodiment will be described below with reference to Figs. 1 to 3. Note that the present disclosure is not limited to the specific embodiment described below. The present disclosure includes various aspects within the spirit or scope of the general disclosed concept as defined by the appended claims.

[0010] As shown in Fig. 1, the capacitor of the embodiment has a capacitor body 1 and an external electrode 3 provided on its end surface. As shown in Fig. 2, the capacitor body 1 has a dielectric layer 5 and an internal electrode layer 7. The dielectric layers 5 and the internal electrode layers 7 are alternately stacked in a plurality of layers. In Fig. 2, the number of stacked dielectric layers 5 and internal electrode layers 7 is simplified to a few layers, but in reality, the number of stacked dielectric layers 5 and internal electrode layers 7 reaches several hundred layers. The external electrode 3 is electrically connected to the internal electrode layers 7.

[0011] The dielectric layer 5 mainly contains a plurality of crystal grains 9 mainly composed of barium titanate. In other words, the dielectric layer 5 is composed of a plurality of crystal grains 9 mainly composed of barium titanate as a matrix 5A. Here, the main component refers to the component that is most abundant in the crystal grains 9. The main component refers to a state in which the crystal grains 9 contain more titanium and barium than other components. The main component refers to the part that has the highest volumetric ratio in the dielectric layer 5 and exhibits the main function. For example, in a capacitor, it refers to a sintered body of crystal grains that are most responsible for the capacitance to be expressed. The matrix 5A is similar in meaning to the main component described above, but if we dare to say it, it refers to the crystal phase that exists in the dielectric layer 5 with the largest volumetric ratio. For example, it refers to the crystal phase that occupies 60% or more of the volumetric ratio in the dielectric layer 5.

[0012] In the capacitor of the embodiment, the dielectric layer 5 contains magnesium, a rare earth element, and manganese in addition to barium titanate. In addition, at least one element selected from magnesium (Mg), rare earth element (RE), and manganese (Mn) is present in the dielectric layer 5 as oxide particles 11 containing a single element. Here, the oxide particles 11 containing a single element means that, for example, in the case of magnesium (Mg), crystal particles mainly composed of magnesium oxide (MgO) are present in the dielectric layer 5 without forming a composite oxide with other metal oxides. The state in which the oxide particles 11 containing one element are present in the dielectric layer 5 means, for example, that when powder X-ray diffraction of the dielectric layer 5 is performed, the diffraction peak of the metal oxide constituting the oxide particles 11 can be confirmed. The metal oxide is in a state in which only one metal element is contained.

[0013] Also, when elemental analysis is performed on the oxide particles 11 seen in the cross section of the dielectric layer 5, the count number of the corresponding element is the highest, and the count number is 10 times or more than that of other elements. Hereinafter, the oxide particles 11 containing at least one element selected from magnesium (Mg), rare earth elements (RE), and manganese (Mn) in a simple form may be referred to as oxide particles 11. Hereinafter, the crystal particles 9 mainly composed of barium titanate may be referred to as main crystal particles 9. The particle diameter of the main crystal particles 9 is preferably 0.05 μm or more and 0.5 μm or less. The rare earth elements (RE) are elements with atomic numbers 57 to 71 shown as lanthanides in the periodic table. Among these, dysprosium (Dy), yttrium (Y), erbium (Er), holmium (Ho), Yb (ytterbium), and Tb (terbium) are preferable. The chemical formulas of dysprosium (Dy), yttrium (Y), erbium (Er), holmium (Ho), Yb (ytterbium) and Tb (terbium) when they become single oxide particles 11 are Dy2O3, Y2O3, Er2O3, Ho2O3, Yb2O3 and Te2O3. Manganese (Mn) is MnO or Mn2O3.

[0014] Oxide particles 11 containing magnesium, rare earth elements, and manganese as simple substances have a higher thermal conductivity than barium titanate crystal particles 9, which is a composite oxide. Therefore, when at least one of magnesium, rare earth elements, and manganese is present as oxide particles 11 containing a simple substance in dielectric layer 5 having barium titanate crystal particles 9 as parent phase 5A, it is possible to improve the heat dissipation from dielectric layer 5 having main crystal particles 9 as parent phase 5A.

[0015] When a DC voltage is continuously applied to a capacitor, the capacitor heats up over time. As the temperature of the capacitor increases, defects such as oxygen vacancies present in the dielectric layer 5 tend to move in the dielectric layer 5. As a result, the insulating properties of the dielectric layer 5 tend to decrease. In addition, the high temperature load life is shortened.

[0016] In contrast, in the capacitor of the embodiment, as described above, oxide particles 11 having a higher thermal conductivity than barium titanate are contained in the dielectric layer 5. This allows the dielectric layer 5 to improve heat dissipation. As a result, even if a DC voltage is continuously applied to the capacitor, the increase in the temperature of the capacitor can be suppressed. This makes it possible to extend the high temperature load life of the capacitor.

[0017] In this case, in the capacitor of the embodiment, the oxide particle 11 preferably has a size such that the diameter D corresponds to the average particle size of the main crystal particle 9. The diameter of the oxide particle 11 is preferably, for example, 0.15 μm or more and 0.3 μm or less. The diameter of the oxide particle 11, 0.15 μm or more and 0.3 μm or less, is the average particle size of each oxide particle 11 contained in the dielectric layer 5. In this case, it is more preferable that the oxide particles having a particle size of 0.15 μm or more and 0.3 μm or less are contained at a rate of 90% or more in terms of number frequency. When the average particle size of the oxide particle 11 is 0.15 μm or more and 0.3 μm or less, the particle size of the oxide particle 11 becomes close to the particle size of the main crystal particle 9. When the size of the oxide particle 11 and the main crystal particle 9 becomes close, as shown in FIG. 3, the oxide particle 11 and the main crystal particle 9 tend to be in contact with each other at the interfacial grain boundary 13. As a result, the contact area between the oxide particle 11 and the main crystal particle 9 becomes large.

[0018] Here, the average particle size of the oxide particles 11 is obtained as follows. First, the capacitor is polished or cut to expose the cross section of the capacitor body 1. Next, the exposed cross section of the capacitor body 1 is polished. Next, the polished cross section of the capacitor body 1 is observed, for example, by a scanning electron microscope equipped with an analyzer, and a photograph of a specific area is taken. At this time, the components of the main crystal particles 9 and the oxide particles 11 are analyzed to identify the main components of the main crystal particles 9 and the oxide particles 11. Next, a region in which the oxide particles 11 are included in the photograph and in which 200 to 300 main crystal particles are contained is specified. Next, from the photograph, the outline of each of the multiple oxide particles 11 present in the region in which 200 to 300 main crystal particles are contained is taken. Next, the outline of each oxide particle 11 is image-processed, and the area of ​​a circle is obtained from the outline. Next, the diameter is obtained from the area of ​​the circle. Finally, the individually obtained diameters are added together to obtain an average value. The average particle size of the oxide particles obtained in this manner can be obtained. The same method is used for the diameter and average particle size of the main crystal particles 9.

[0019] As shown in FIG. 3, when the cross section of the dielectric layer 5 is viewed in plan, for example, when the main crystal grains 9 are circular or polygonal in shape, the oxide grains 11 preferably include those having a shape equivalent to that of the grain boundary phase 15 formed by a plurality of main crystal grains 9 adjacent to each other. Here, the shape of the oxide grains 11 corresponding to the shape of the grain boundary phase 15 refers to the shape when the dielectric layer 5 is viewed in cross section. The main crystal grains 9 being circular means that the contour of the main crystal grains 9 is generally rounded, and when the longest diameter of the main crystal grains 9 is the maximum diameter D1 and the direction perpendicular to the direction of the maximum diameter D1 is the minimum diameter D2, the ratio D1 / D2 is 1 or more and 1.1 or less. The main crystal grains 9 being polygonal means that the contour of the main crystal grains 9 has at least two straight sides in a part of the contour.

[0020] The shape of the oxide particle 11 corresponding to the shape of the grain boundary phase 15 is, for example, the shape of a region between two or more adjacent main crystal grains 9. In other words, it is a shape that fills the space between two or more adjacent main crystal grains 9. The shape of the oxide particle 11 corresponding to the shape of the grain boundary phase 15 may include shapes that are difficult to give a specific name to, but for example, the following shapes can be given as examples. In this case, the terms representing the shape of the oxide particle 11 are each given a symbol. As shown in FIG. 3, the shapes are a circle (symbol 11a), a polygon (11b), a triangle (11c), a square (11d), an ellipse (11e), a potbellied shape (11f), an arrowhead shape (11g), and an uneven shape (11h) in which a constriction (11ha) and a body (11hb) are connected. The dielectric layer 5 may contain oxide particles 11 having a shape in which a plurality of shapes given symbols 11a to 11h are combined. Here, the potbellied shape 11f refers to a shape in which a large particle portion 11fa having a large volume is joined to a small particle portion 11fb having a smaller volume than the large particle portion 11fa. The arrowhead shape 11g refers to a shape that is basically triangular, but has one end that is pointed and the other end that is rounded or flat. In this case, the arrowhead shape 11 g includes a shape in which two of the three sides are slightly curved outwardly in a convex shape. The uneven shape 11h in which the constricted portion 11ha and the body portion 11hb are connected is basically a long, thin band shape, but the constricted portion 11ha and the body portion 11hb are connected in the longitudinal direction. In this case, the body portion 11hb also includes a shape that bulges outward.

[0021] When the shape of the oxide particle 11 corresponds to the shape of the grain boundary phase 15 formed by a plurality of main crystal grains 9 adjacent to each other, the oxide particle 11 can be in a state of partially surrounding the periphery of the main crystal grain 9. 9 By being interposed between adjacent main crystal grains, 9 This indirectly increases the contact area between the capacitor and the heat transfer coefficient, thereby improving the thermal conductivity of the capacitor.

[0022] In the capacitor of the embodiment, the ratio of oxide particles 11 contained in the dielectric layer 5 is preferably 0.5% or more and 5% or less, and particularly 1.5% or more and 3% or less. The ratio of oxide particles 11 shown here is a value determined from the diffraction intensity ratio of the X-ray pattern of powder obtained by crushing the dielectric layer 5 or the capacitor, as described below. In this case, the diffraction intensity I0 of the main peak (index 110) of barium titanate constituting the main crystal grains 9 and the ratio of oxide particles 11 After determining the diffraction intensity I1 of the main peak (index 111), the diffraction intensity ratio I1 / I0 is determined. .child In this case, when the diffraction intensity ratio is 0.5% or more, the oxide particles 11 have an effect on the thermal conduction to the dielectric layer 5. When the diffraction intensity ratio is 3% or less, the decrease in the relative dielectric constant of the dielectric layer 5 is suppressed, so that the capacitor can maintain a high capacitance.

[0023] In the capacitor of the embodiment, the oxide particles 11 are preferably present in the capacitor body 1 in a region other than the internal electrode layer 7. When the oxide particles 11 are present in the entire capacitor body 1 in a region other than the internal electrode layer 7, the thermal conductivity is increased everywhere in the capacitor body 1, and the heat dissipation performance can be further improved.

[0024] Next, a method for manufacturing the capacitor of the embodiment will be described. The capacitor of the embodiment can be manufactured by a conventional manufacturing method for a capacitor, except that a predetermined proportion of pre-calcined raw powder is added to the ceramic green sheet for forming the dielectric layer 5 as the raw powder of magnesium, rare earth elements, and manganese, which are additives, and the temperature rise rate in the main firing is made higher than usual and fired for a short time. If a pre-calcined raw powder is used as an additive to be added to the raw powder of barium titanate, the additive is likely to remain in the dielectric layer 5 as a simple metal oxide after the main firing. In this case, it is better to increase the temperature rise rate during the main firing within a range that does not impair the sinterability of the dielectric layer 5. Since the time during which the capacitor body 1 is exposed to a high-temperature environment is shortened, the proportion of the additive remaining in the simple metal oxide after the main firing is increased. In this way, oxide particles containing at least one element selected from magnesium, rare earth elements, and manganese as a simple substance, together with crystal particles 9 mainly composed of barium titanate, are formed in the dielectric layer 5. 11 can be present. EXAMPLES

[0025] The capacitors were specifically manufactured and their characteristics were evaluated as follows. First, barium titanate powder and glass powder were prepared as raw powders for preparing the dielectric powder. For the barium titanate powder, raw powder with an average particle size of 0.05 μm was used. For the glass powder, a composition of SiO2=55, BaO=20, CaO=15, and Li2O=10 (mol%) was used. For the raw powders of additives, magnesium oxide powder and manganese carbonate powder were prepared. In addition, rare earth element oxide powders were prepared. The compositions of the rare earth element oxide powders are shown in Table 1. The average particle sizes of the magnesium oxide powder and manganese carbonate powder were 0.1 μm. The average particle size of the rare earth element oxide powder was 0.05 μm. Of these raw powders, for samples No. 1 to No. 20, rare earth element oxide powders that were calcined in air at a maximum temperature of 850° C. and a holding time of 2 hours were used. The Y2O3 powder used for sample No. 21 had an average particle size of 0.1 μm. The Y2O3 powder used for sample No. 21 was a raw material powder that had not been subjected to a calcination treatment.

[0026] The dielectric powder was made by adding 0.5 moles of magnesium oxide powder (calculated as MgO) and 0.5 moles of manganese carbonate powder (calculated as MnO) to 100 moles of barium titanate powder, and further adding 1 part by mass of glass powder to 100 parts by mass of barium titanate powder. The amount of rare earth element oxide powder added is shown in Table 1.

[0027] Next, the dielectric powder was mixed with an organic vehicle, and the prepared slurry was used to prepare ceramic green sheets with an average thickness of 2.8 μm by doctor blade method. A butyral-based resin was used as the resin to be contained in the organic vehicle when preparing the ceramic green sheets. The amount of butyral-based resin added was 10 parts by mass per 100 parts by mass of barium titanate powder. A solvent in which ethyl alcohol and toluene were mixed at a mass ratio of 1:1 was used. A conductive paste containing nickel powder was used as the conductive paste for forming the internal electrode pattern.

[0028] Next, a conductive paste was printed on the ceramic green sheet to prepare a pattern sheet. Next, 400 layers of the pattern sheet were laminated to prepare a core laminate. Next, ceramic green sheets were laminated on the upper and lower sides of the core laminate to prepare a base laminate. After this, the base laminate was cut to prepare a compact of the capacitor body.

[0029] Next, the capacitor body was produced by firing the green body of the capacitor body. The maximum temperature in the firing was 1100°C, the holding time was 10 minutes, and the heating rate was 2000°C / h. A roller hearth kiln was used for firing. Next, the produced capacitor body was subjected to a re-oxidation treatment. The conditions for the re-oxidation treatment were a nitrogen atmosphere, a maximum temperature of 950°C, and a holding time of 5 hours. The size of the obtained capacitor body was 2 mm × 1.2 mm × 1.2 mm. The average thickness of the dielectric layer was 2 μm. The average thickness of the internal electrode layer was 0.8 μm. The design value of the capacitance of the produced capacitor was set to 11 μF.

[0030] Next, the capacitor body was barrel polished, and then an external electrode paste mainly composed of copper powder was applied to both ends of the capacitor body, followed by heat treatment at 800°C in a nitrogen atmosphere to form the external electrodes. After this, nickel plating and tin plating were formed on the surfaces of the external electrodes to obtain the capacitor.

[0031] In addition, a separate sample with the same composition as sample No. 5 was prepared by setting the heating rate during firing at 10,000°C / h. In this case, the ratio of rare earth element oxide particles confirmed in the dielectric layer of the obtained capacitor was small, but instead, magnesium (magnesium oxide) and manganese oxide (Mn2O3) were confirmed to be contained in the dielectric layer as single oxide particles. The X-ray diffraction peak ratio R2O3(111) / BT(110) for the rare earth element oxide particles of this sample was 0.3%.

[0032] In addition, a composite oxide of rare earth elements and titanium oxide (pyrochlore: RE2Ti2O7) was synthesized, and a capacitor was similarly produced by adding this composite oxide. The capacitor produced using the composite oxide of rare earth elements and titanium oxide (pyrochlore: RE2Ti2O7) has the following characteristics: 1 to Among the samples shown, these are samples Nos. 8 to 10, 12, 14, 16, 18 and 20.

[0033] Next, the fabricated capacitors were evaluated as follows. First, the electrical characteristics of the obtained capacitors were measured. The electrostatic capacitance was measured using a capacitance measuring device (Agilent 4284A). The measurement conditions were an AC voltage of 0.5 V and a frequency of 1 kHz. The high temperature load life was measured under the conditions of a temperature of 125°C, an applied DC voltage of 40 V, and a retention time of up to 200 hours. Within 200 hours, no short circuit (resistance was 10 1 Samples that showed a resistance of 100Ω or less were deemed defective (failed). Thermal shock resistance was evaluated by immersing the sample in a heated solder bath. The temperature of the solder bath was set to a temperature difference of 280°C from room temperature (25°C). The immersion time was 1 minute. After immersion in the solder bath, samples that showed signs of cracking were counted as defective.

[0034] The average grain size of the main crystal grains, the shape of the oxide grains, and the average grain size of the oxide grains were determined using a scanning electron microscope equipped with an analyzer by the following method. First, the middle part in the lamination direction and the center part in the width direction were selected from the cross section of the polished cross section of the capacitor body, and an area of ​​5 μm in the width direction and 5 μm in the thickness direction was specified. Next, the components of the crystal grains found in that area were identified. The crystal grains forming the parent phase were barium titanate.

[0035] Furthermore, oxide particles containing simple rare earth elements were present in the matrix. The diameter D of the oxide particles was determined as follows. First, the cross section of the dielectric layer was exposed. Next, the exposed cross section was mirror-polished. The polished cross section of the dielectric layer was observed using a scanning electron microscope, and a photograph of a specific area was taken. Next, an area was specified on the photograph that contained oxide particles and contained 200 to 300 main crystal particles. Next, the outlines of each of the multiple oxide particles present in that area were drawn by hand from the photograph. The outline of each oxide particle was subjected to image processing, and the area of ​​a circle was determined from the outline. Next, the diameter was determined from the area of ​​the circle. Next, the average value of the diameter values ​​determined from the multiple oxide particles was determined. Table 1 shows this average value as the average particle diameter (D RE The average grain size of the main crystal grains (D BT ) and the average particle size of the pyrochlore crystal grains were calculated in the same manner. RE / D BT " is the average grain size (D BT ) to the average particle size of oxide particles (D RE ) is the ratio of

[0036] In the capacitors corresponding to the present disclosure among the samples prepared, oxide particles with cross-sectional shapes of more than half of the following types were observed: circular (reference numeral 11a in FIG. 3), polygonal (11b), triangular (11c), square (11d), elliptical (11e), pot-shaped (11f), arrowhead (11g), and uneven shape (11h) in which the constricted portion (11ha) and the body portion (11hb) are connected. In particular, oxide particles with polygonal (11b), triangular (11c), square (11d), elliptical (11e), pot-shaped (11f), arrowhead (11g), and uneven shape (11h) in which the constricted portion (11ha) and the body portion (11hb) are connected were confirmed.

[0037] The content of oxide particles in the dielectric layer was determined by the following method using an X-ray diffraction device. First, the external electrodes were removed from the manufactured capacitor, and the capacitor was processed into its main body. Next, the capacitor from which the external electrodes had been removed was pulverized to prepare a sample in powder form. At this time, care was taken to remove as much metal components as possible from the powder. Next, X-ray diffraction was performed on the powder obtained. As peaks for determining the diffraction intensity ratio, a peak with index (110) was specified for barium titanate, and a peak with index (111) was specified for oxide particles of rare earth elements. The diffraction intensity ratios are shown in the "Diffraction Intensity Ratio RE2O3(111) / BT(110)" column in Table 1. The diffraction intensity ratio for pyrochlore is also shown in Table 1. 。 This is the column in Table 1 titled “Diffraction intensity ratio RE2Ti2O7(222) / BT(110).”

[0038] [Table 1]

[0039] As is clear from the results in Table 1, the samples (samples Nos. 1 to 7, 11, 13, 15, 17, and 19) in which it was confirmed that one element was present as oxide particles in the dielectric layer, had a defect rate of 1 or less per 100 in the high temperature load life test. Also, the defect rate in the thermal shock resistance test was 1 or less per 100.

[0040] Among these samples, samples in which the average particle size, determined by converting the outline of the oxide particle into a circle, was 0.15 μm or more and 0.3 μm or less (samples Nos. 1 to 3, 5, 6, 11, 13, 15, 17, and 19) had a capacitance of 10.1 μF or more.

[0041] In addition, samples (samples Nos. 3 to 6, 11, 13, 15, 17 and 19) in which the proportion of oxide particles contained in the dielectric layer was an intensity ratio of 1.5% or more and 3% or less, calculated based on the main peak of barium titanate from powder X-ray diffraction of the dielectric layer, showed no defects in the high-temperature loaded life test.

[0042] In addition, a capacitor in which the dielectric layer contained magnesium (magnesium oxide) and manganese oxide (Mn2O3) in addition to rare earth element oxide particles as oxide particles containing a single element had a capacitance of 10.1 μF and only 2 out of 100 units had defects in high-temperature load life tests.

[0043] On the other hand, in the samples containing pyrochlore crystal particles (samples Nos. 8 to 10, 12, 14, 16, 18 and 20), the number of defects in the high temperature load life test was 3 or more per 100 samples.

[0044] In addition, in the sample (sample No. 21) in which yttrium oxide powder was used as the rare earth oxide without calcination, composite oxides of rare earth element (Y) and Si were scattered in the dielectric layer, but the presence of oxide particles of simple element Y2O3 could not be confirmed. In addition, the number of defectives in the high temperature load life test was 5 out of 100.

[0045] The present disclosure may have the following embodiments.

[0046] The capacitor of the present disclosure includes a capacitor body in which dielectric layers and internal electrode layers are alternately laminated in multiple layers, and the dielectric layers are mainly composed of multiple crystal particles whose main component is barium titanate, and contain magnesium, rare earth elements, and manganese, with at least one of the magnesium, rare earth elements, and manganese being present as oxide particles containing the element as a single substance.

[0047] The present disclosure can be implemented in various other forms without departing from its spirit or main features. Therefore, the above-described embodiments are merely examples in all respects, and the scope of the present disclosure is indicated in the claims and is not limited in any way by the text of the specification. Furthermore, all modifications and changes falling within the scope of the claims are within the scope of the present disclosure. [Explanation of symbols]

[0048] 1. Capacitor body 3····External electrodes 5. Dielectric layer 5A···Maternal phase 7····Internal electrode layer 9····Main crystal particles 11···Acidide particles 13···Dihedral grain boundary 15···Grain boundary phase

Claims

1. The capacitor body is made up of multiple layers of dielectric layers and internal electrode layers laminated alternately. the dielectric layer is mainly composed of a plurality of crystal grains having barium titanate as a main component, and contains magnesium, a rare earth element, and manganese; The rare earth element is contained as oxide particles containing the rare earth element as a simple substance, a ratio of the oxide particles to the barium titanate contained in the dielectric layer is 1.5% or more and 3% or less in terms of an intensity ratio determined by powder X-ray diffraction based on a main peak of barium titanate; The amount of the raw material powder of the oxide particles is 1.6 to 3.2 moles per 100 moles of the barium titanate powder which is the raw material of the main component barium titanate.

2. The capacitor of claim 1 , wherein the oxide particles are present in the capacitor body except for the internal electrode layers.

Citation Information

Patent Citations

  • Laminated ceramic capacitor

    JP2011132056A

  • Dielectric ceramic composition, method for producing the same and ceramic electronic part

    JP2012072037A

  • Multilayer ceramic electronic component

    JP2019087568A

  • Capacitor

    WO2017073621A1